Donor‐derived, metastatic urothelial cancer after kidney transplantation associated with a potentially oncogenic BK polyomavirus. Issue 3 (1st February 2018) - Müller, David C; Rämö, Maarit; Naegele, Klaudia; Ribi, Sebastian; Wetterauer, Christian; Perrina, Valeria; Quagliata, Luca; Vlajnic, Tatjana; Ruiz, Christian; Balitzki, Beate; Grobholz, Rainer; Gosert, Rainer; et al.
Abstract: BK polyomavirus has been linked to urothelial carcinoma in immunosuppressed patients. Here, we performed comprehensive genomic analysis of a BK polyomavirus‐associated, metachronous, multifocal and metastatic micropapillary urothelial cancer in a kidney transplant recipient. Dissecting cancer heterogeneity by sorting technologies prior to array‐comparative genomic hybridization followed by short tandem repeat analysis revealed that the metastatic urothelial cancer was of donor origin (4‐year‐old male). The top 50 cancer‐associated genes showed no key driver mutations as assessed by next‐generation sequencing. Whole genome sequencing and BK polyomavirus‐specific amplification provided evidence for episomal and subgenomic chromosomally integrated BK polyomavirus genomes, which carried the same unique 17‐bp deletion signature in the viral non‐coding control region (NCCR). Whereas no role in oncogenesis could be attributed to the host gene integration in chromosome 1, the 17‐bp deletion in the NCCR increased early viral gene expression, but decreased viral replication capacity. Consequently, urothelial cells were exposed to high levels of the transforming BK polyomavirus early proteins large tumour antigen and small tumour antigen from episomal and integrated gene expression. Surgery combined with discontinuation of immunosuppression resulted in complete remission, but sacrificed the renal transplant. Thus, this report links, for the first time, BK polyomavirus NCCR rearrangements with oncogenic transformation in urothelial cancer in immunosuppressed patients. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.